Effectiveness of perioperative oral hygiene management using a cetylpyridinium chloride‐, dipotassium glycyrrhizinate, and tranexamic acid‐based mouthwash as an adjunct to mechanical oral hygiene in patients with maxillomandibular fixation: A randomized controlled clinical trial - Reona Aijima; Yoshio Yamashita (Wiley, 2023)
Abstract Objectives Maxillomandibular fixation requires the jawbones to remain static. Mechanical cleaning is also carried out by brushing or with a water flosser to maintain the oral cavity in a hygienic state, but this cannot be considered sufficient. Mouthwashes are used as a substitute for mechanical cleaning or in a supplementary role after such cleaning. The aim is to evaluate the effectiveness of HABITPRO mouthwash, which contains cetylpyridinium chloride, dipotassium glycyrrhizinate, and tranexamic acid in the specific environment created by maxillomandibular fixation used as an adjunct to mechanical cleaning. Material and Methods A total of 55 patients who had undergone maxillomandibular fixation were randomly allocated to either a HABITPRO group (n = 29) or a placebo group (n = 26). To investigate their oral hygiene status, their plaque control record (PCR) was reviewed, and the caries‐related bacterial counts, pH, acid buffering capacity, white blood cell count, and ammonia in saliva were measured immediately before maxillomandibular fixation, on Day 10 of fixation, and immediately after fixation was released. Results After approximately 2-3 weeks of mouthwash use, the PCR index also increased significantly in the placebo group compared with baseline, whereas it remained almost steady in the HABITPRO group. Additionally, salivary ammonia levels decreased significantly in the HABITPRO group compared to that of the placebo group. Conclusions Even with maxillomandibular fixation, continued gargling with HABITPRO mouthwash in the perioperative period as an adjunct to mechanical cleaning can help maintain better oral hygiene and reduce bacterial counts.